Processo de formação de recursos humanos da saúde e o ensino das disciplinas vinculadas à estatística: das intenções aos gestos - Carneiro, Wendell Soares (2020)
Decision-making processes among professionals, especially health professionals, are quite common, but not always so simple, since they are meticulous and analytical procedures. In the process of training these professionals, decision making is always worked on in the disciplines linked to statistics, therefore, it is necessary for students to seize the content, as well as the way to implement it. The study aimed to investigate the teaching-learning process of subjects linked to statistics in the training of human resources for health. It was an exploratory, observational study in the health courses of a Higher Education Institution to verify the decision-making processes and the teaching-learning process in view of the disciplines that underlie this process in those courses. Correspondence and grouping analyzes were used for analysis. It was observed that most of the participants considered the workload for these disciplines to be insufficient, as well as not considering themselves able to implement such methods in the day-to-day of their profession. It is concluded that, among learners, there is still a difficulty to understand the interdependence relationship between the two processes, decision making and teaching-learning, with this, the deficiency in resizing and reallocating the work forces and inputs available in the health remains, thus generating a persistence in the maintenance of old problems and an under-utilization of the workforce, as well as the instruments available in the services.